Pressure-sensitive adhesive for polaroid as well as preparation method and application of pressure-sensitive adhesive

By using high-temperature-resistant pressure-sensitive adhesive equipped with acrylic resin, curing agent, catalyst, silane coupling agent and antistatic agent in the polarizer, and controlling its maturation conditions, the problem of bubbles caused by shrinkage and deformation of the polarizer pressure-sensitive adhesive at high temperature is solved, and the high-temperature performance of the polarizer is significantly improved.

CN119799211AActive Publication Date: 2025-04-11WANHUA CHEM GRP CO LTD
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202510001537.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-02
Publication Date
2025-04-11
Estimated Expiration
2045-01-02

AI Technical Summary

Technical Problem

Under high temperature conditions, the pressure-sensitive adhesive in the polarizer is too deformed due to shrinkage stress and crosslinking, which is prone to cracks and bubbles, affecting the performance of the polarizer.

Method used

A high-temperature-resistant polarizer pressure-sensitive adhesive is used, which contains acrylic resin, curing agent, catalyst, silane coupling agent and antistatic agent. By controlling the ratio of the catalyst to the curing agent and the temperature and time during the maturation process, the shrinkage value of the pressure-sensitive adhesive at high temperature is within 5%.

Benefits of technology

It effectively reduces the bubble phenomenon caused by high-temperature shrinkage and improves the high-temperature weather resistance and stability of the polarizer.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
  • Figure FDA0005225383360000021
    Figure FDA0005225383360000021
Patent Text Reader

Abstract

The invention relates to a pressure-sensitive adhesive for a polaroid and a preparation method and application of the pressure-sensitive adhesive, and the formula of the pressure-sensitive adhesive comprises the following components in percentage by mass: 90-99.5% of acrylic resin; 0.01-1% of a curing agent; 0.001 to 1% of a catalyst; 0.02 to 0.8 percent of a silane coupling agent; and 0.05-3% of an antistatic agent. The pressure-sensitive adhesive has shrinkage deformation resistance at high temperature. When the pressure-sensitive adhesive is used for preparing the polaroid, the shrinkage value c of the pressure-sensitive adhesive at high temperature is within 5% by controlling the relationship among the parameters in the curing process, and the bubble phenomenon generated by high-temperature shrinkage can be reduced.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to polarizer preparation technology, and in particular to a pressure-sensitive adhesive for polarizer and its preparation method and application. Background Art

[0002] Pressure-sensitive adhesive is a type of adhesive that is sensitive to pressure. The three most commonly used types are rubber-based pressure-sensitive adhesive, acrylate-based pressure-sensitive adhesive, and silicone-based pressure-sensitive adhesive. Pressure-sensitive adhesive (PSA) has been widely used in many fields, especially in the field of polarizers. In the composition structure of polarizers, pressure-sensitive adhesive is one of the core materials for preparing polarizers. The pressure-sensitive adhesive used in polarizers is mainly acrylate-based pressure-sensitive adhesive, which is synthesized by copolymerization of various acrylate monomers.

[0003] The structure of the polarizer is two layers of triacetyl cellulose (TAC) film sandwiched by a layer of stretched polyvinyl alcohol (PVA) film, which is bonded to the liquid crystal display glass substrate by a pressure-sensitive adhesive. Under high temperature conditions, the polyvinyl alcohol (PVA) film and even the entire polarizer shrink, causing the pressure-sensitive adhesive to be subjected to a large shrinkage stress. In addition, the continuous cross-linking of the colloid under high temperature conditions also produces shrinkage stress. During the shrinkage and deformation process of the colloid, if the deformation is too large, it will cause the colloid to cohesively break, produce cracks, and then generate bubbles.

[0004] Therefore, it is necessary to develop a pressure-sensitive adhesive for polarizers that is resistant to shrinkage and deformation at high temperatures to prevent bubbles from being generated during the shrinkage and deformation process of the colloid. Summary of the invention

[0005] In order to solve the above problems, the present invention provides a pressure-sensitive adhesive for polarizer and a preparation method thereof. The pressure-sensitive adhesive has the ability to resist shrinkage and deformation at high temperatures. When used to prepare polarizers, the shrinkage value c of the pressure-sensitive adhesive at high temperature is controlled within 5% by controlling the relationship between various parameters during the curing process, which can reduce the bubble phenomenon caused by high-temperature shrinkage.

[0006] In order to achieve the above technical effects, the present invention adopts the following technical solutions:

[0007] The present invention provides a high temperature resistant pressure sensitive adhesive for polarizer, wherein the formula of the pressure sensitive adhesive comprises the following components in percentage by weight:

[0008] Acrylic resin 90-99.5%, for example, 90%, 92%, 94%, 95%, 96%, 97%, 98%, 99%, 99.5%, etc.;

[0009] Curing agent 0.01-1%, for example 0.01%, 0.05%, 0.1%, 0.3%, 0.5%, 0.8%, 1%, etc.;

[0010] Catalyst 0.001-1%, for example 0.001%, 0.005%, 0.01%, 0.05%, 0.1%, 0.3%, 0.5%, 0.8%, 1%, etc.;

[0011] Silane coupling agent 0.02-0.8%, for example, 0.02%, 0.05%, 0.08%, 0.1%, 0.3%, 0.5%, 0.8%, etc.;

[0012] Antistatic agent 0.05-3%, for example 0.05%, 0.08%, 0.1%, 0.5%, 1%, 0.5%, 2%, 2.5%, 3% and the like.

[0013] In one embodiment, the acrylic resin is a copolymer of acrylic monomers containing hydroxyl groups and / or carboxyl groups, and has a molecular weight (Mw) of 1 million to 2.5 million, preferably 1.5 million to 2 million;

[0014] The acrylic monomer containing hydroxyl and / or carboxyl groups is selected from one or more of 4-hydroxybutyl (meth)acrylate, 2-hydroxyethyl (meth)acrylate, 2-hydroxypropyl chloroacrylate, crotonic acid, methacrylic acid, itaconic acid, etc., preferably one or more of 4-hydroxybutyl (meth)acrylate and methacrylic acid;

[0015] The acrylic monomer is a known product in the art and can be a common commercial product directly purchased or prepared by technicians according to the prior art. The present invention has no special requirements. For example, in actual applications, it can be prepared by referring to the method disclosed in patent CN107924009 A.

[0016] In one embodiment, the curing agent is at least one of an isocyanate curing agent and an epoxy curing agent, preferably an isocyanate curing agent;

[0017] The isocyanate curing agent is preferably at least one of toluene diisocyanate, diphenylmethane diisocyanate, and 1,6-hexane diisocyanate;

[0018] The epoxy curing agent is preferably at least one selected from polyethylene glycol diglycidyl ether, glycerol diglycidyl ether, and ethylene glycol glycidyl ether, and more preferably ethylene glycol glycidyl ether.

[0019] In one embodiment, the catalyst includes, but is not limited to, an organic amine catalyst;

[0020] The organic amine catalyst includes but is not limited to at least one of triethylenediamine, N,N-dimethylcyclohexylamine and triethylamine, preferably triethylenediamine.

[0021] The formula of the high temperature resistant pressure sensitive adhesive for polarizer of the present invention further contains silane coupling agent and antistatic agent, which are additives conventionally used for products of this type and can be conventionally selected in the field without special requirements. For example, the raw material types listed below can be used;

[0022] The silane coupling agent is selected from at least one of the silicon compounds containing unsaturated groups such as methacryloxypropyltrimethoxysilane, vinyltriethoxysilane, vinyltrimethoxysilane, etc., and is more preferably vinyltriethoxysilane;

[0023] The antistatic agent is selected from one or more of surfactant substances and ionic compound substances, preferably ionic compound substances, and more preferably at least one of 1-ethylpyrrole hexafluorophosphate, tributylmethylammonium bisfluorosulfonimide, and 1-octyl-4-methylpyrrole hexafluorophosphate.

[0024] The above-mentioned pressure-sensitive adhesive for high temperature resistant polarizer of the present invention may further include a solvent in its formula;

[0025] The solvent is selected from one or more of ethyl acetate and methyl acetate;

[0026] The amount of the solvent added is 15-25% based on the total dry basis mass of the pressure-sensitive adhesive for high temperature resistant polarizer, for example 15%, 17%, 20%, 22%, 25%, etc. The dry basis of the pressure-sensitive adhesive for high temperature resistant polarizer refers to acrylic resin, curing agent, catalyst, silane coupling agent and antistatic agent.

[0027] The invention provides a method for preparing a pressure-sensitive adhesive for a polarizer, which is obtained by adopting conventional physical blending in the field.

[0028] For example, the components in the above formula are weighed according to the mass percentage and then mixed evenly to obtain the pressure-sensitive adhesive for polarizer.

[0029] The present invention also provides an application method of the pressure-sensitive adhesive for polarizer. In the process of using the pressure-sensitive adhesive for preparing polarizer, by controlling the relationship between the ratio of catalyst and curing agent, aging temperature and aging time, the shrinkage value (c) of the pressure-sensitive adhesive at high temperature can be kept within 5%, thereby reducing the bubble phenomenon caused by high-temperature shrinkage of the polarizer.

[0030] It should be noted that the shrinkage value (c) described in the present invention is the difference between ba, wherein a represents the gel fraction of the pressure-sensitive adhesive film layer when the curing is completed, and b represents the gel fraction of the pressure-sensitive adhesive film layer after the curing is continued to be placed at 80°C for 3-5 days (generally 4 days in actual testing).

[0031] The gel fraction described in the present invention is tested by referring to the steps for testing the gel fraction of the pressure-sensitive adhesive layer provided in patent CN 115236262 A, which will not be described in detail in the present invention.

[0032] Specifically, a method for applying a pressure-sensitive adhesive for a polarizer, when using the pressure-sensitive adhesive for preparing a polarizer, comprises the following steps:

[0033] S1: coating the polarizer on a release film with a pressure-sensitive adhesive, and drying and curing the polarizer;

[0034] S2: Laminating the original polarizer film on the release film coated with the pressure-sensitive adhesive in step S1 and curing the film to obtain a dry pressure-sensitive adhesive film.

[0035] Wherein, the release film in step S1 is a polyethylene terephthalate release film.

[0036] Among them, the pressure-sensitive adhesive for polarizer in step S1 has a mass ratio (m) of catalyst to curing agent in the formula of 1:1 to 1:1000, for example, 1:1, 1:10, 1:50, 1:100, 1:150, 1 to 300, 1 to 500, 1 to 800, 1 to 900, 1 to 1000, etc., preferably 1:20 to 200.

[0037] Wherein, in step S1, the drying and curing temperature is 70-120°C, for example, 70°C, 80°C, 90°C, 100°C, 110°C, 120°C, etc., preferably 90-100°C; the curing time is 3-10min, for example, 3min, 5min, 7min, 9min, 10min, etc., preferably 4-6min.

[0038] Among them, in the aging step S2, the aging temperature (T) is 25 to 60°C, for example, 25°C, 30°C, 40°C, 50°C, 60°C, etc., and the aging time (t) is 2 to 180 days, for example, 2 days, 10 days, 30 days, 50 days, 70 days, 100 days, 130 days, 150 days, 180 days, etc.

[0039] The pressure-sensitive adhesive dry film obtained after the aging in step S2 has a thickness of 10 to 40 μm, such as 10 μm, 20 μm, 30 μm, 40 μm, etc., preferably 20 to 30 μm.

[0040] In steps S1 and S2, the ratio of catalyst to curing agent (m), aging temperature (T), and aging time (t) are controlled to satisfy the following relationship:

[0041]

[0042] In the present invention, the gel fraction value a of the dry film after the aging in step S2 is tested;

[0043] Then the cured dry film is placed at 80°C for 3-5 days to test the gel fraction value b;

[0044] The difference between the gel fraction b and the gel fraction a (ba) is calculated to obtain the shrinkage value c of the pressure-sensitive adhesive for polarizer under high temperature conditions.

[0045] In the present invention, the shrinkage value c of the polarizer pressure-sensitive adhesive under high temperature conditions can be controlled within 5%. Under 80° C., the number of bubbles generated by the polarizer PSA is controlled to be 3 / 50 cm or less.

[0046] Compared with the prior art, the present invention has the following beneficial effects:

[0047] The pressure-sensitive adhesive for polarizer of the present invention controls the ratio of curing agent to catalyst (m), and the aging temperature (T) and aging time (t) of the curing process to meet a certain relationship, thereby reasonably controlling the shrinkage value of the colloid itself under high temperature conditions to be within 5%, thereby reducing the number of bubbles generated by the polarizer PSA due to high-temperature shrinkage. DETAILED DESCRIPTION

[0048] In order to facilitate the understanding of the present invention, the present invention will be further described below in conjunction with examples. It should be understood that the following examples are only for a better understanding of the present invention and do not mean that the present invention is limited to the following examples.

[0049] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those commonly understood by those skilled in the art to which the invention belongs. The term "and / or" as may be used herein includes any and all combinations of one or more of the associated listed items.

[0050] Where specific experimental steps or conditions are not specified in the examples, the corresponding conventional experimental steps or conditions in the art can be used. The reagents or instruments used without specifying the manufacturer are all conventional products that can be purchased commercially.

[0051] In each embodiment and comparative example of the present invention, the sources of the main raw materials used are as follows:

[0052] Acrylic resin: prepared by the method disclosed in patent CN 107924009 A.

[0053] Toluene diisocyanate, diphenylmethane diisocyanate, 1,6-hexanediisocyanate, polyethylene glycol diglycidyl ether, glycerol diglycidyl ether, ethylene glycol glycidyl ether, tributylmethylammonium bis(fluorosulfonyl)imide, ethyl acetate, methyl acetate, triethylenediamine, N,N-dimethylcyclohexylamine, and triethylamine were from Beijing Inokai Technology Co., Ltd.;

[0054] 1-Ethylpyrrole hexafluorophosphate and 1-octyl-4-methylpyrrole hexafluorophosphate were from Adamas; 1-octyl-4-methylpyrrole hexafluorophosphate was from Zhengzhou Aikemu Chemical Co., Ltd.

[0055] Main test methods

[0056] The gel fraction test method refers to patent CN 115236262 A.

[0057] Number of bubbles generated in weathering test: The size of the weathering test sample is 230×130mm. After being attached to the glass plate, it is placed at 80℃ for 1000 hours. Using a metallographic microscope with a magnification of 50 times, observe the bubbles generated at the edge of the sample and record the number of bubbles.

[0058] Example 1

[0059] 99.5% of acrylic resin (molecular weight of 1.93 million), 0.1% of toluene diisocyanate curing agent, 0.005% of organic amine catalyst triethylenediamine, 0.195% of silane coupling agent vinyl triethoxysilane, and 0.2% of antistatic agent 1-ethylpyrrole hexafluorophosphate are mixed by mass percentage, and then mixed with solvent ethyl acetate accounting for 20wt% of the total mass of the above raw materials to obtain a pressure-sensitive adhesive for polarizer, wherein the mass ratio m) of the catalyst to the curing agent is 1:20.

[0060] The polarizer pressure-sensitive adhesive was coated on a polyethylene terephthalate release film and dried and cured at 80°C for 5 minutes. The original polarizer film was then laminated on the release film coated with the pressure-sensitive adhesive and placed in an environment of (T) 60°C for aging. The aging t was calculated to be 4 days. After the aging, a pressure-sensitive adhesive dry film (film thickness of 20 μm) was obtained, and the gel fraction value a was tested.

[0061] The cured pressure-sensitive adhesive dry film was placed at 80° C. for another 4 days, the gel fraction value b was tested, and the shrinkage value c=ba was calculated.

[0062] The pressure-sensitive adhesive dry film was bonded to a glass substrate and tested for weather resistance at 80°C. The number of bubbles at the edge was observed after 1000 hours.

[0063] The results are shown in Table 1 below.

[0064] Example 2

[0065] 98.14% of acrylic resin (molecular weight of 1.64 million), 1% of 1,6-diisocyanate curing agent, 0.01% of organic amine catalyst N,N-dimethylcyclohexylamine, 0.8% of silane coupling agent methacryloxypropyl trimethoxysilane, and 0.05% of antistatic agent tributylmethylammonium bis(fluorosulfonyl)imide are mixed by mass percentage, and then mixed with solvent ethyl acetate accounting for 15wt% of the total mass of the above raw materials to obtain a pressure-sensitive adhesive for polarizer, wherein the mass ratio (m) of the catalyst to the curing agent is 1:100.

[0066] The polarizer was coated with pressure-sensitive adhesive on a polyethylene terephthalate release film and dried and cured at 70°C for 10 min. The original polarizer film was then attached to the release film coated with the pressure-sensitive adhesive and placed in an environment of (T) 50°C for aging. The aging t was calculated to be 8 days. After the aging, a pressure-sensitive adhesive dry film (film thickness of 20 μm) was obtained, and the gel fraction value a was tested.

[0067] The cured pressure-sensitive adhesive dry film was placed at 80° C. for another 5 days, the gel fraction value b was tested, and the shrinkage value c=ba was calculated.

[0068] The pressure-sensitive adhesive dry film was bonded to a glass substrate and tested for weather resistance at 80°C. The number of bubbles at the edge was observed after 1000 hours.

[0069] The results are shown in Table 1 below.

[0070] Example 3

[0071] 90.46% of acrylic resin (molecular weight of 1.48 million), 8% of diphenylmethane diisocyanate curing agent, 0.04% of organic amine catalyst triethylamine, 0.5% of silane coupling agent vinyltrimethoxysilane, and 1% of antistatic agent 1-octyl-4-methylpyrrole hexafluorophosphate are mixed by mass percentage, and then mixed with solvent methyl acetate accounting for 25wt% of the total mass of the above raw materials to obtain a pressure-sensitive adhesive for polarizer, wherein the mass ratio (m) of the catalyst to the curing agent is 1:200.

[0072] The polarizer pressure-sensitive adhesive was coated on a polyethylene terephthalate release film and dried and cured at 100°C for 4 minutes. The original polarizer film was then attached to the release film coated with the pressure-sensitive adhesive and placed in an environment of (T) 30°C for aging. The aging t was calculated to be 13 days. After the aging, a pressure-sensitive adhesive dry film (film thickness of 20 μm) was obtained, and the gel fraction value a was tested.

[0073] The cured pressure-sensitive adhesive dry film was placed at 80° C. for another 3 days, the gel fraction value b was tested, and the shrinkage value c=ba was calculated.

[0074] The pressure-sensitive adhesive dry film was bonded to a glass substrate and tested for weather resistance at 80°C. The number of bubbles at the edge was observed after 1000 hours.

[0075] The results are shown in Table 1 below.

[0076] Example 4

[0077] 99.44% of acrylic resin (molecular weight of 1.09 million), 0.05% of ethylene glycol glycidyl ether curing agent, 0.01% of organic amine catalyst triethylamine, 0.4% of silane coupling agent vinyl trimethoxysilane, and 0.1% of antistatic agent tributyl methyl ammonium bis(fluorosulfonyl)imide are mixed by mass percentage, and then mixed with solvent methyl acetate accounting for 20wt% of the total mass of the above raw materials to obtain a pressure-sensitive adhesive for polarizer, wherein the mass ratio (m) of the catalyst to the curing agent is 1:5.

[0078] The polarizer pressure-sensitive adhesive was coated on a polyethylene terephthalate release film and dried and cured at 110°C for 3 min. The original polarizer film was then attached to the release film coated with the pressure-sensitive adhesive and placed in an environment of (T) 25°C for aging. The aging t was calculated to be 3 days. After the aging, a pressure-sensitive adhesive dry film (film thickness of 20 μm) was obtained, and the gel fraction value a was tested.

[0079] The cured pressure-sensitive adhesive dry film was placed at 80° C. for another 4 days, the gel fraction value b was tested, and the shrinkage value c=ba was calculated.

[0080] The pressure-sensitive adhesive dry film was bonded to a glass substrate and tested for weather resistance at 80°C. The number of bubbles at the edge was observed after 1000 hours.

[0081] The results are shown in Table 1 below.

[0082] Comparative Example 1

[0083] Referring to the method provided in Example 1, the difference is that no catalyst is used, other operations and conditions remain unchanged, and the results are shown in Table 1.

[0084] Comparative Example 2

[0085] Referring to the method provided in Example 1, the difference is that: 0.00005wt% of the organic amine catalyst triethylenediamine is used in the formula, wherein the mass ratio (m) of the catalyst to the curing agent is 1:2000. The results are shown in Table 1.

[0086] Comparative Example 3

[0087] Referring to the method provided in Example 1, the difference is that the original polarizer film is laminated on a release film coated with a pressure-sensitive adhesive, and placed in an environment of (T) 60°C for aging, and the aging t is 2 days (i.e., t does not use the calculated aging days). The results are shown in Table 1.

[0088] The shrinkage value of the pressure-sensitive adhesive itself and the bubble situation generated by high temperature weathering under different formulation conditions were tested in the embodiments of the present invention and the comparative examples. The test results are shown in Table 1 below:

[0089] Table 1

[0090]

[0091] It can be seen from the data in the table that the preparation method of the high temperature resistant polarizer of the present invention controls the aging time according to the catalyst ratio and the aging temperature, thereby reasonably controlling the gel fraction of the colloid before bonding and use, reducing the shrinkage value caused by the colloid itself during the high temperature process, and effectively improving the high temperature weather resistance of the colloid during actual use, and avoiding the generation of bubbles at the edge of the polarizer. .

[0092] It is easy to understand that the above embodiments are only examples for clear explanation and do not mean that the present invention is limited thereto. For ordinary technicians in the relevant field, other different forms of changes or modifications can be made based on the above description. It is not necessary and impossible to list all the implementation methods here. The obvious changes or modifications derived from this are still within the protection scope of the present invention.

Claims

1. A high temperature resistant pressure sensitive adhesive for polarizer, characterized in that: The formula contains the following components in percentage by weight: Acrylic resin 90~99.5%; Curing agent 0.01~1%; Catalyst 0.001~1%; Silane coupling agent 0.02~0.8%; Antistatic agent 0.05~3%.

2. The high temperature resistant pressure sensitive adhesive for polarizer according to claim 1, characterized in that: The acrylic resin is a copolymer of acrylic monomers containing hydroxyl groups and / or carboxyl groups, and has a molecular weight of 1 million to 2.5 million, preferably 1.5 million to 2 million; Among them, the acrylic monomer containing hydroxyl and / or carboxyl groups is selected from one or more of (meth)acrylate-4-hydroxybutyl ester, (meth)acrylate-2-hydroxyethyl ester, chloro-2-hydroxypropyl acrylate, crotonic acid, methacrylic acid, itaconic acid, etc., preferably one or more of (meth)acrylate-4-hydroxybutyl ester and methacrylic acid.

3. The high temperature resistant pressure sensitive adhesive for polarizer according to claim 1, characterized in that: The curing agent is at least one of an isocyanate curing agent and an epoxy curing agent, preferably an isocyanate curing agent; Preferably, the isocyanate curing agent is preferably at least one of toluene diisocyanate, diphenylmethane diisocyanate, and 1,6-hexane diisocyanate; Preferably, the epoxy curing agent is at least one selected from polyethylene glycol diglycidyl ether, glycerol diglycidyl ether, and ethylene glycol glycidyl ether, and more preferably ethylene glycol glycidyl ether.

4. The high temperature resistant pressure sensitive adhesive for polarizer according to claim 1, characterized in that: The catalyst is selected from organic amine catalysts; Preferably, the organic amine catalyst is at least one of triethylenediamine, N,N-dimethylcyclohexylamine and triethylamine, more preferably triethylenediamine; and / or The silane coupling agent is at least one selected from the group consisting of methacryloxypropyltrimethoxysilane, vinyltriethoxysilane, vinyltrimethoxysilane and other silicon compounds containing unsaturated groups, more preferably vinyltriethoxysilane; and / or The antistatic agent is selected from one or more of surfactant substances and ionic compound substances, preferably ionic compound substances, and more preferably at least one of 1-ethylpyrrole hexafluorophosphate, tributylmethylammonium bisfluorosulfonimide, and 1-octyl-4-methylpyrrole hexafluorophosphate.

5. The high temperature resistant pressure sensitive adhesive for polarizer according to claim 1, characterized in that: Solvents are also added to its formula; Preferably, the solvent is selected from one or more of ethyl acetate and methyl acetate; Preferably, the added amount of the solvent is 15-25% based on the total dry weight of the pressure-sensitive adhesive for high temperature resistant polarizer.

6. A method for applying the high temperature resistant pressure sensitive adhesive for polarizer according to any one of claims 1 to 5, characterized in that: When it is used to prepare a polarizer, the steps include: S1: coating the polarizer on a release film with a pressure-sensitive adhesive, and drying and curing the polarizer; S2: Laminating the original polarizer film on the release film coated with the pressure-sensitive adhesive in step S1 and curing the film to obtain a dry pressure-sensitive adhesive film.

7. The application method according to claim 6, characterized in that: The release film in step S1 is a polyethylene terephthalate release film; and / or The pressure-sensitive adhesive for polarizer in step S1 has a mass ratio (m) of catalyst to curing agent of 1:1 to 1:1000, preferably 1:20 to 200; and / or In step S1, the drying and curing is carried out at a curing temperature of 70 to 120° C., preferably 90 to 100° C.; and the curing time is 3 to 10 minutes, preferably 4 to 6 minutes.

8. The application method according to claim 6, characterized in that: In step S2, the aging temperature (T) is 25 to 60° C. and the aging time (t) is 2 to 180 days; and / or The pressure-sensitive adhesive dry film obtained after the aging in step S2 has a thickness of 10 to 40 μm, preferably 20 to 30 μm.

9. The application method according to any one of claims 6 to 8, characterized in that: In steps S1 and S2, the ratio of catalyst to curing agent (m), aging temperature (T), and aging time (t) are controlled to satisfy the following relationship:

10. The application method according to claim 6, characterized in that: The shrinkage value of the pressure-sensitive adhesive for the polarizer under high temperature conditions is controlled within 5%.

Citation Information

Patent Citations

  • Adhesive layer for polarizing plates and adhesive composition

    CN107924009A

  • Acrylic copolymer, pressure-sensitive adhesive, preparation method and application of pressure-sensitive adhesive in polaroids

    CN112708008A

  • Ultraviolet curing pressure-sensitive adhesive for polaroid

    CN113549412A

  • Pressure-sensitive adhesive and polaroid for vehicle-mounted equipment

    CN115746753A

  • Heat-resistant acrylic resin, acrylic pressure-sensitive adhesive for polaroid protective film and preparation method of acrylic pressure-sensitive adhesive

    CN117777350A